Journey to heaven and to hell - Davies, Rodney (London : Robert Hale, 2002)
While death, that great and inexorable leveller, lies ahead of us all, it is but a staging post on this journey we call life. Beyond death is the next realm, wherein that which survives our physical body, the soul or wraith, continues to exist, perhaps indefinitely.